A methodical approach to the pre-match training of goalkeepers in beach soccer - Privalov A.V. ,; Nifontov M.Yu. ,; Mukhamedzyanov R.R. ,; Dmitriev I.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to creation and validation of a holistic framework for the training of elite goalkeepers in beach soccer prior to competitions. Methods and structure of the study. Analysis of special literature and documents; pedagogical observations; pedagogical testing; goniometry; psychophysiological diagnostics (simple visual-motor reaction (hereinafter SMVMR), reaction to a moving object (hereinafter RMO), discrimination reaction (hereinafter DR) and choice reaction (hereinafter CR)); modeling; pedagogical experiment; methods of mathematical statistics. The practical testing of the model of pre-competitive training of goalkeepers in beach soccer was carried out on the basis of two leading professional football clubs: PFC Kristall (St. Petersburg) and PFC Lokomotiv (Moscow). A comprehensive verification of the developed model was carried out with the participation of 24 highly qualified football players in the experiment. Results and conclusions. The framework of the proposed model for pre-competitive goalkeeping training in beach soccer encompasses elements that consider: the temporal dimensions of implementation (spanning two to four weeks); the characteristics of specialized training (horizontal physical training, its individualization, including the biomechanical aspects of each player); the complexity of the training regimen; the adaptability to specific training loads; and the practical application. The overall proficiency of the goalkeeper is a crucial factor in the success of the entire team during the competitive period. The proposed model also takes into account the unique aspects of transferring various technical skills from football to beach soccer, as well as the implementation of these skills in the challenging environment of the sand court.